Environmental issues and risks at Casa de Piedra Tourist Villa, La Pampa province, Argentina (Huellas, 2023)
The Casa de Piedra Tourist Villa is the youngest town in the country and its foundation is associated to the proximity of a dam inaugurated in 1996 in the middle course of the Colorado River. In this way, the development of an artificial lake led to productive projects dependent on irrigation and a residential and commercial area with tourist purposes. However, it was not possible to mate-rialize all the proposals promoted by the provincial government. Consequently, as part of a research project of the POIRE of the UNLPam, an interdisciplinary study was carried out in order to determine if the environmental issues generated, especially from 2019, have had local consequences. To this end, official statistics analysis, comparisons with sanitary parameters, field surveys, impact identification studies, and interviews with key informants were carried out. As a conclusion, it was confirmed that the modification of the multipurpose plans drawn up by the provincial government in 2006 is based on the historical downspout of the river and other factors of a regional or local nature, includ-ing salinization and pollution. They worsen the water problem and affect living conditions. Therefore, some political decisions should be reconsidered in terms of territorial planning and management.
Keywords: Casa de Piedra; Colorado River; multipurpose projects; environmental issues; decision-makers